Analysis Of Semiotics Representation Of Feminism In The Mulan Film 2020 - Br Sinuraya, July Susanti; Azhar, Anang Anas; Sazali, Hasan (International Journal of Cultural and Social Science, 2022)
This research is entitled Semiotic Analysis of Feminism Representation in Mulan Film 2020. The purpose of this research is to find out how the semiotic analysis of feminism representation in Mulan 2020 film. The theory used to analyze this research is semiotic theory. The object of the research is Film Mulan 2020, an American period war action drama film directed by Niki Caro. It is a live-action remake of the 1998 animated film produced by Disney. The method used in this study is a qualitative method with the semiotic analysis technique of the Roland Barthes model. The results of the study indicate that there are several scenes depicting the representation of feminism in the film 3 Mulan 2020 which have been studied through Roland Barthes' Semiotics theory. The representation of feminism can be seen from the signs and meanings that have been studied through Roland Barthes' Semiotics theory.